Two new tetracyclic triterpenoids from the barks of Melia azedarach. Issue 1 (2nd January 2016) - Ge, Jun-Jun; Wang, Ling-Tian; Chen, Pian; Zhang, Yan; Lei, Xin-Xiang; Ye, Xiao-Xia
Abstract: Two new tetracyclic triterpenoids, together with 21 known compounds, were isolated from the barks of Melia azedarach . The structures of new compounds were elucidated by the means of HRESIMS, 1D NMR, 2D NMR, and X-ray crystallography analysis.